Cardiotoxicity After Anthracycline Chemotherapy for Childhood Cancer in a Multiethnic Asian Population - Tan, Varen Zhi Zheng; Chan, Nicole Min; Ang, Wai Lin; Mya, Soe Nwe; Chan, Mei Yoke; Chen, Ching Kit (Frontiers in Pediatrics, 2021)
Background: Anthracyclines are widely used to treat childhood cancers; however, they cause cardiotoxicity. To address the paucity of clinical data from Asian populations, this study investigated the epidemiology of pediatric anthracycline-induced cardiotoxicity, during and after chemotherapy, in a multiethnic Asian population. Procedure: This was a single-center, retrospective analysis of 458 anthracycline-treated pediatric oncology patients at KK Women's and Children's Hospital, a tertiary children's hospital in Singapore from 2005 through 2015. We investigated cardiotoxicity (defined as left ventricular fractional shortening <28% on echocardiography) and its risk factors using univariate logistic regression as well as survival estimates through the Kaplan-Meier method to compare survival distribution between patients with and without cardiotoxicity. Results: Over a follow-up period of almost 4 years, we found that 7% (32/458) of the cohort developed cardiotoxicity, with 37.5% (12/32) of these manifesting as clinical heart failure, whilst the rest were asymptomatic. The cardiotoxic cohort demonstrated a significantly higher mortality rate compared to the non-cardiotoxic group at 46.9 vs. 19.2% (p < 0.001), of whom 3 (9.4%) died from end-stage heart failure. We found that traditional predictors such as female sex, age at diagnosis, and cumulative doxorubicin equivalent dose were not predictors of cardiotoxicity. Conclusion: Our study reaffirms that freedom from symptoms does not ensure normal heart function and suggests that children with abnormal ventricular systolic function have higher mortality risk compared to those with normal systolic function. The findings contribute to improved understanding of the Asian burden to aid development of measures to prevent or reduce the risk of cardiotoxicity.